2021
DOI: 10.3389/fphys.2021.590638
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic Profiling to Reveal Potential Biomarkers for the Diagnosis of Fatty Liver Hemorrhagic Syndrome in Laying Hens

Abstract: Fatty liver hemorrhage syndrome (FLHS), a nutritional and metabolic disease that frequently occurs in laying hens, causes serious losses to the poultry industry. Nowadays, the traditional clinical diagnosis of FLHS still has its limitations. Therefore, searching for some metabolic biomarkers and elucidating the metabolic pathway in vivo are useful for the diagnosis and prevention of FLHS. In the present study, a model of FLHS in laying hens induced by feeding a high-energy, low-protein diet was established. Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…By measuring the changes of metabolites, metabolomics offers fresh insights into the disease pathogenesis ( Johnson et al., 2016 ). With the application of gas chromatography-mass spectrometry based metabolomics, the researchers found that some liver metabolites participated in FLHS ( Zhuang et al., 2019 ), and serum metabolites could be used in the clinical diagnosis of FLHS ( Guo et al., 2021 ). Due to the high resolution, powerful separation and excellent sensitivity, ultraperformance liquid chromatography-quadrupole time-of-flight mass spectrometry ( UPLC-QTOF/MS ) has been proved to be an indispensable technique for metabonomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…By measuring the changes of metabolites, metabolomics offers fresh insights into the disease pathogenesis ( Johnson et al., 2016 ). With the application of gas chromatography-mass spectrometry based metabolomics, the researchers found that some liver metabolites participated in FLHS ( Zhuang et al., 2019 ), and serum metabolites could be used in the clinical diagnosis of FLHS ( Guo et al., 2021 ). Due to the high resolution, powerful separation and excellent sensitivity, ultraperformance liquid chromatography-quadrupole time-of-flight mass spectrometry ( UPLC-QTOF/MS ) has been proved to be an indispensable technique for metabonomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Monoacylglycerols metabolism is also related to the effects of endocannabinoids in the immune system ( Chiurchiu et al, 2015 ). 3-HB is one of the ketone bodies serving as a biomarker to reflect fatty acid β-oxidation and ketogenic amino acid catabolism ( Choi et al, 2020 ; L.; Guo et al, 2021 ). 3-HB was also found to be associate with excess glutathione demand and disrupted mitochondrial energy mechanisms, occurring during persistent oxidative stress ( Volani et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples were prepared according to our previous protocol with modification ( 36 , 37 ), and then were submitted to Biotree Biotech Co., Ltd. (Shanghai, China) for detecting the metabolite concentrations by UPLC-Q-TOF/MS analysis. The bioinformatics analysis was performed according to the standard protocols of Biotree Biotech Co., Ltd.…”
Section: Methodsmentioning
confidence: 99%